Workplace Stressors Burnout Quiet Quitting Organizational Social Dynamics - Sitti Mukarromah (Journal Economic Business Innovation, 2026)
Purpose— The paper’s aim is to make a contribution to research in management and accounting by examining "quiet quitting" as abehavioral response to long-term stressors in the workplace. It also considers the implications of this for performance management,human capital accountability, and organizational value creation. This study draws on resource conservation theory, the Job Demands–Resources model, and the social-contextual approach to discuss how unfavorable management and job design conditions can lead to "quiet quitting" through psychological and social processes.Design/methodology/approach — We conducted a quantitative study and analysed survey research data using a partial least squaresstructural equation model to evaluate an integrative framework linking workplace stressors, burnout, quiet quitting, and socialinteraction intensity. The model shows how managerial control practices, job design realities, and accountability-related stressorscan lead to behavioral disengagement.Findings—The results show that long-term work stressors are linked to quiet quitting via burnout. This highlights burnout as a key psychological process through which managerial pressure and job demands lead to a decrease in discretionary effort. Furthermore, stressors’ explanatory power is not limited to fatigue; quiet quitting also reflects workers’ assessments of managerial practices and perceived effort-reward imbalances. The level of social interaction intensity does not significantly influence this relationship.Furthermore, high interaction frequency does not appear to compensate for structural (managerial) inadequacies.Originality/value—This paper provides insights into the management and accounting literature by reconceptualizing quiet quittingas a result of ill-aligned control, workload distribution, and relational job design, rather than an individual attitudinal shortcoming.It’s a fresh behavioral-accountability lens that connects HR management, job design, and performance governance to today’strends in disengagement.